2006
DOI: 10.1002/hep.21091
|View full text |Cite
|
Sign up to set email alerts
|

Progression of liver fibrosis among injection drug users with chronic hepatitis C

Abstract: Although most hepatitis C virus (HCV) infections are acquired by injection drug use, prospective data on the progression of liver fibrosis are sparse. Baseline liver biopsies were obtained (1996-1998) on a random sample of 210 out of 1667 HCV-positive injection drug users (IDUs). Subjects were followed biannually, with a second biopsy offered to those eligible. Paired biopsies were scored 0 to 6 (modified Ishak score), significant fibrosis was defined as score 3 or greater, and progression of fibrosis was defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 37 publications
(51 reference statements)
2
58
0
1
Order By: Relevance
“…22,42 We have also previously reported that liver enzyme values are lower when HCV-infected persons have been injecting in the preceding months. 43 Interestingly, we found that active injection drug use was associated with higher levels of protective EndoCAb IgM, which bind LPS.…”
Section: Discussionmentioning
confidence: 84%
“…22,42 We have also previously reported that liver enzyme values are lower when HCV-infected persons have been injecting in the preceding months. 43 Interestingly, we found that active injection drug use was associated with higher levels of protective EndoCAb IgM, which bind LPS.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, HCV viral load was the only factor with a statistically significant association with mild fibrosis compared to no fibrosis. Two recent paired biopsy studies of individuals with chronic HCV infection and predominantly mild fibrosis identified HCV viral load as an independent predictor of fibrosis progression (29,31). These results suggest that the relationship between HCV viral load and risk of fibrosis progression warrants reevaluation, with a focus on those persons with minimal or mild HCV disease.…”
Section: Discussionmentioning
confidence: 89%
“…Although these predictive values appear suboptimal, the NPV was more acceptable in lower prevalence settings, such as typically observed in community-based cohorts. 64 For example, at a prevalence of 30% to 40%, the estimated NPV ranged from 80% to 86%; at the same time, the PPV did not exceed 52% (Fig. 3).…”
Section: Discussionmentioning
confidence: 91%